Zakres podmiotowy i klasyfikacja pojęcia „podmiot ekonomii społecznej” - Małecka-Łyszczek, Magdalena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
Taking into consideration the need to undertake in-depth analysis in the area of the identification of entities belonging to the social economy sector as well as in recognizing the deficit of literature of the subject in this matter - the subject of this article was examined the scope of the subjective concept of "social economy entity". Qualifications were made, resulting in their emergence and subsequent discussion: 1. Social enterprises as the core and point of reference for further divisions, 2. Other social economy entities and 3, entities forming the social economy. The presented classifications were made with the knowledge that they must be open due to innovative solutions characteristic for the social economy sector and its constant growth.
Keywords: social economy; entities forming the social economy; social enterprise